The Cemetery of Hala Sultan Tekke, Cyprus: Further Evidence of Interculturality and Burial Customs in the Late Bronze Age - Fischer, Peter M. (Near Eastern archaeology, 2024)
This study deals with the results from the 2018-2023 fieldwork at the cemetery of Hala Sultan Tekke. The aim of the project is the safeguarding, excavation, recording, and study of tombs exposed to farming, erosion, and looting. The stratigraphy of the tombs that were used over generations represents an excellent complement to the sequence of occupation in the city. The mortuary gifts and personal belongings date mainly to the fifteenth to thirteenth centuries BCE and confirm far-reaching trade, further underlining the role of the city as a trading center in the Mediterranean economic system. The material evidence corroborates connections with societies of the Mycenaean, Minoan, Hittite, Levantine, and Egyptian spheres of culture as well as networks with regions as far away as Sardinia, the Baltic Sea, Mesopotamia, Afghanistan, and India. In addition, several find contexts provide valuable information about the complex mortuary customs of the Late Cypriot period., *Warning: This article deals with human bones.